Pravna narava socialnega varstva v sistemu socialne varnosti - Strban, Grega (Podjetje in delo, 2021)
The social assistance system is not very often legally analysed part of the law of social security. Because of the rather scarce legal research in this field, terms like social security, social assistance, social protection, social advantage and social compensation might be wrongly used. Nevertheless, there are quite important substantive distinctions concerning the legal nature and responsible parties hiding behind the veil of those terms. Only by knowing the distinctions, and diligently using the established terms, can enable the correct choice of individual measures in the mentioned fields, proper understanding of the EU law and law of the Member States, as well as their successful use in jurisprudence and application in legal practice. Especially during times of economic distress in society, the social assistance system is rather prone to numerous modifications.
Keywords: sistem socialne varnosti; social advantage; social assistance; social compensation; social protection; socialna odškodnina; socialna pomoč; socialna ugodnost; socialna zaščita; socialno varstvo